A Sure Thing? Online Gaming and Canada - Rodenberg, Ryan M.; Holden, John T. (DigitalCommons@Pace, 2013)
The legal status of gaming activities on First Nations land within Canada is complicated. The foci of this paper are two-fold. First, we trace the origin and expansion of First Nations gaming. Second, we analyze the potential of First Nations as hubs for the growing global e-gaming industry, with an emphasis on Internet poker and online sports wagering. We conclude by positing that the Canadian regulatory scheme presents an opportunity to First Nations in connection with e-gaming.